Alternative strategies of for-profit, not-for-profit and state-owned Nepalese microfinance institutions for poverty alleviation and women empowerment - Bharat Ram Dhungana; Ramkrishna Chapagain; Arvind Ashta (Cogent Economics & Finance, 2023)
Microfinance is the provision of financial services to disadvantaged people and the financially excluded, often with a social mission of poverty alleviation and women empowerment. There are many different forms of microfinance institutions (MFIs): for-profit, not-for-profit and state-owned, all of which use different strategies to improve socio-economic status of their clients. The objective of this paper is to examine the alternative strategies of MFIs in Nepal. Primary data was collected through structured questionnaires from 240 women clients of three MFIs. Parametric and non-parametric tests, and exploratory factor analysis have been applied for analysis. The results show that MFIs have different segmentation strategies for their clients, focusing on income levels, total consumption and the number of children. Surprisingly, it was found that the private MFI was reaching poorer people than other MFIs. Our results show that MFIs look at total consumption expenditure rather than total income. Private MFIs target different activities for giving loans compared to government-owned MFIs. The communication strategy of the MFIs is different since the clients of government-owned MFI are better educated and are more likely to read the newspaper. The exploratory factor analysis shows that respondents perceived poverty alleviation and empowerment. The most influencing factors are related to an increase in consumption expenditure, followed by an increase in capital expenditure.
Keywords: G21; L25; L31; L32; O53; P36; 330; creating shared value; Microfinance institutions; segmenting; strategy; targeting